(untitled) (Research Nepal Journal of Development Studies, 2021)
Tantrism is the science of practical spiritualism. Tantrism is the practical way out of enlightenment. It is the perfect mix of theoretical and empirical knowledge of liberation. Although there are different arguments for and against tantric Buddhism. To find out the basic overview of Tantric Buddhism the study has been conducted. It is a literature review of Tantric Buddhism in Nepal. In conclusion, the study found that there is a great contradiction between Buddhist philosophy with the law of cause and effect. It is difficult to make ritual action conform to such a law, as he demonstrated.